Diversity of arbuscular mycorrhizal fungi in mimosa invisa and effect of the soil ph on the symbiosis - Kittiworawat S. (2014)
Mimosa invisa is widely distributed in Northern Thailand. M. invisa is a leguminous weed which is used as green manure for increasing soil fertility and organic matter. They are colonized by arbuscular mycorrhizal (AM) fungi which increase nutrient uptake by the plant. In addition, roots of M. invisa are nodulated with Rhizobium bacteria that fix N 2 from the atmosphere. The objectives of this research are (1) to study diversity of AM fungi in M. invisa in cultivated, uncultivated and seasonally wet areas in Chiang Mai province (2) to evaluate the effect of soil pH (4.0, 5.0 and 6.0) on AM spore production in two varieties of M. invisa (thornless and thorny mimosa) and (3) the effect of AM fungi on the host plant in a pot experiment. Twenty-three species of AM fungi were found in the root zones of M. invisa in the study areas. The highest spore density occurred in uncultivated areas, slightly lower in cultivated areas and lowest in seasonally wet areas. In the pot experiment, AM fungi significantly increased dry weight, nutrient contents (N, P and K) in shoot, root and N in nodule in all treatments. The soil pH had effect on root colonization and spore density. The optimal soil pH for root colonization and spore production of AM fungi was pH 5.0 associated with both varieties of M. invisa. Root colonization in thornless mimosa and thorny mimosa in the soil pH 5.0 was 88% and 80%, respectively. The highest spore density in soil pH 5.0 of thornless mimosa was 16.3 spores g -1 soil while thorny mimosa was 7.3 spores g -1 soil. Thornless mimosa had root colonization and spore density of AM fungi higher than thorny mimosa. Therefore, in addition to the ease in handling without the sharp little thorns, the thornless mimosa is more suitable for using as green manure and as natural inoculum of AM fungi in agriculture than thorny mimosa.